Three‐Dimensional Turbulence‐Resolving Modeling of the Venusian Cloud Layer and Induced Gravity Waves: Inclusion of Complete Radiative Transfer and Wind Shear. Issue 10 (27th October 2018) - Lefèvre, M.; Lebonnois, S.; Spiga, A.
Abstract: Venus' convective cloud layers and associated gravity waves strongly impact the local and global budget of heat, momentum, and chemical species. Here we use for the first time three‐dimensional turbulence‐resolving dynamical integrations of Venus' atmosphere from the surface to 100‐km altitude, coupled with fully interactive radiative transfer computations. We show that this enables to correctly reproduce the vertical position (46‐ to 55‐km altitude) and thickness (9 km) of the main convective cloud layer measured by Venus Express and Akatsuki radio occultations, as well as the intensity of convective plumes (3 m/s) measured by VEGA balloons. Both the radiative forcing in the visible and the large‐scale dynamical impact play a role in the variability of the cloud convective activity with local time and latitude. Our model reproduces the diurnal cycle in cloud convection observed by Akatsuki at the low latitudes and the lack thereof observed by Venus Express at the equator. The observed enhancement of cloud convection at high latitudes is simulated by our model, although underestimated compared to observations. We show that the influence of the vertical shear of horizontal superrotating winds must be accounted for in our model to allow for gravity waves of the observed intensity (>1 K) and horizontal wavelength (up to 20 km) to be generated through the obstacle effect mechanism. The vertical extent of our model also allows us to predict for the first time a 7‐km‐thick convective layer at the cloud top (70‐km altitude) caused by the solar absorption of the unknown ultraviolet absorber. Plain Language Summary: The Venus convective cloud layers and associated gravity waves impact on the local and global budget of heat, momentum, and chemical species remains unclear. Here we use for the first time three‐dimensional turbulence‐resolving dynamical integrations of Venus' atmosphere from the surface to 100‐km altitude, coupled with fully interactive radiative transfer computations. We show that this enables to correctly reproduce the vertical position (46‐ to 55‐km altitude) and thickness (9 km) of the main convective cloud layer. Our model reproduces the diurnal cycle in cloud convection observed by Akatsuki at the low latitudes and the lack thereof observed by Venus Express at the equator. The observed enhancement of cloud convection at high latitudes is simulated by our model, although underestimated compared to observations. We show that the influence of the vertical shear of horizontal superrotating winds must be accounted for in our model to allow for gravity waves of the observed intensity and horizontal wavelength to be generated through the obstacle effect mechanism. Key Points: First 3‐D turbulence‐resolving model of the Venus atmosphere coupled with interactive radiative scheme Strong impact of the horizontal wind vertical shear on the gravity waves amplitude and wavelengths The 7‐km convective activity resolved at cloud top due to solar absorption of the unknown UV absorber